2011
DOI: 10.1590/s0482-50042011000600006
|View full text |Cite
|
Sign up to set email alerts
|

Influência da interação entre qualidade ambiental e o SNP T102C do gene HTR2A sobre a suscetibilidade à fibromialgia

Abstract: Objectives: This study aimed to investigate the genetic infl uence of the T102C polymorphism of the 2A serotonin receptor gene (HTR2A) and its interaction with environmental aspects, such as exposure to noise, traffi c, climate, and opportunities to acquire new information, physical protection, and security, among others, as possible risk factors for developing fi bromyalgia syndrome (FMS). Methods: Forty-one FMS patients and 49 controls were evaluated. Environmental factors were evaluated by application of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
(26 reference statements)
0
4
0
1
Order By: Relevance
“…Several studies have shown that specific genes related to the serotonergic system are also involved in the pathogenesis of FM. The frequency of carriers of the 102C allele of the 2A serotonin receptor gene (HTR2A) was significantly higher in patients with FM than in the control group, and FM patients had worse perceptions of environmental factors [20]. A meta-analysis also confirmed that the 102T/C polymorphism of the 5-HT2A receptor was linked to FM [21].…”
Section: ) Genetics and Epigenetics (1) Genetic Factorsmentioning
confidence: 89%
“…Several studies have shown that specific genes related to the serotonergic system are also involved in the pathogenesis of FM. The frequency of carriers of the 102C allele of the 2A serotonin receptor gene (HTR2A) was significantly higher in patients with FM than in the control group, and FM patients had worse perceptions of environmental factors [20]. A meta-analysis also confirmed that the 102T/C polymorphism of the 5-HT2A receptor was linked to FM [21].…”
Section: ) Genetics and Epigenetics (1) Genetic Factorsmentioning
confidence: 89%
“…Mergener et al [21] analyzed the influence of the interaction between environmental quality and the SNP in the gene HTR2A 102 T/C on the susceptibility of developing fibromyalgia in 41 patients with fibromyalgia and 49 control individuals, and showed that carriers of the C allele summed up to the variable low quality of health and social care, presented a risk 90 times greater of developing the syndrome (p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…There is need for further investigations to a better understanding of the role of polymorphism in the serotonin receptor gene HTR2A in origin and/or severity of fibromyalgia. Lee et al [20] and Mergener et al [21] found an association between fibromyalgia and the polymorphism of the gene 102 T/C, demonstrating that the carriers of the C allele present higher risk for the development of the syndrome. However, studies like those of Tander et al [26] and Matsuda et al [27] found no statistically significant relationship among the polymorphisms 102 T/C and -1438A/G and fibromyalgia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Há evidências que polimorfismos não específicos em circuitos serotoninérgicos, dopaminérgicos, ou ainda catecolaminérgicos, estejam ligados à etiopatogenia da doença (MATSUDA et al, 2010). Recentemente, Mergener relatou um provável efeito do SNPT102C no gene do receptor HTR2A no metabolismo da 5-HT, mas ainda faltam estudos para explicar todos os genes envolvidos na fisiopatologia da doença (MERGENER et al, 2011…”
Section: Considerações Genéticasunclassified